Overview of extracellular vesicles in pathogens with special focus on human extracellular protozoan parasites - Alvarado Ocampo, Johan (2024)
Extracellular vesicles (EVs) are lipid-bilayered membrane-delimited particles secreted by almost any cell type, involved in different functions according to the cell of origin and its state. From these, cell to cell communication, pathogen-host interactions and modulation of the immune response have been widely studied. Moreover, these vesicles could be employed for diagnostic and therapeutic purposes, including infections produced by pathogens of diverse types; regarding parasites, the secretion, characterisation, and roles of EVs have been studied in particular cases. Moreover, the heterogeneity of EVs presents challenges at every stage of studies, which motivates research in this area. In this review, we summarise some aspects related to the secretion and roles of EVs from several groups of pathogens, with special focus on the most recent research regarding EVs secreted by extracellular protozoan parasites.